Dampak Pemutihan Karang Tahun 2016 Terhadap Ekosistem Terumbu Karang: Studi Kasus Di TWP Gili Matra (Gili Air, Gili Meno dan Gili Trawangan) Provinsi NTB Coral Bleaching Impact in 2016 Towards Coral Reef Ecosystem: Case Studies TWP Gili Matra (Gili Air, - Fakhrizal Setiawan; Azhar Muttaqin; S.A. Tarigan; M Muhidin; H Hotmariyah; Abdus Sabil; Jessica Pinkan (Jurnal Kelautan, 2017)
ABSTRACTIncreased sea surface temperatures due to global warming that occurred from the early to mid 2016 caused of coral bleaching in several locations in TWP Gili Matra. Observations of coral bleaching  obtained from coral colonies compotition affected by bleaching (50%), white (18%), death (1%) and was not affected (31%). These implications resulting decline in coral cover but not significant (F (1,013) = 0.333, p 0.05) from 23,43% ± 2,61 SE in 2012 to 18,48% ± 4,14 SE in 2016 and a significant decrease (P (58,06) = 3,8e-06) recruitment of coral (coral Juvenil) from 6,66 ind.m-1 ± 1,04 SE in 2012 to 1,41 ind.m-1 ± 0,16 SE in 2016. the other impact is a significant reduction (P(20.84) = 0,00053, p 0,001) the abundance of reef fish from 28.733,26 ind.ha-1 ± 3.757,89 SE in 2012 to 11.431,18 ind.ha-1 ± 702,53 SE in 2016 and a decline in the biomass of reef fish but not significant (F (0,58) = 0,46, P 0.05) from 506,56 kg.ha-1 ± 99,05 SE in 2012 to 438,41 kg.ha-1 ± 45,69 SE in 2016. The decline of coral recruitment resulted in the recovery of the affected areas bleaching becomes slow because of the juvenile new coral mostly dead. The second impact of bleaching is an abundance of fish decrease, indicating that is available only fish big size (adult) and very less of small fishes, including juvenile. Keywords: global warming, coral bleaching, coral cover, reef fishes